Modeling the antecedents of integration of ethnomathematical perspectives into geometry teaching among faculty: A logistic regression analysis - Kyeremeh, Patrick; Awuah, Francis Kwadwo; Orey, Daniel Clark (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
The necessity for establishing links between school mathematics and students' personal lives and cultures, as enshrined in the ethnomathematics program, is being recognized and investigated in different regions across the globe. However, a comprehensive understanding of the antecedents that drive the integration of ethnomathematical perspectives into mathematics teaching among mathematics teachers is still limited. This cross-sectional survey aimed to address this gap by investigating whether the explanatory variables (such as gender, teaching experience, and religion) predict the mathematics teacher educators’ incorporation of the mathematics found outside of school into geometry teaching. We included a sample of 128 mathematics teacher educators in the survey through non-probability sampling. A logistic regression model was employed to analyze the data garnered using a web-based questionnaire. Based on the findings, all three explanatory variables (gender, teaching experience, and religion) did not predict mathematics teacher educators’ incorporation of mathematics found outside of school into geometry teaching. The findings would help key actors of mathematics education to re-examine their beliefs and practices about the incorporation of ethnomathematical perspectives into teaching that builds on students’ socio-cultural experiences. Implications for teaching and future research are reported.